2015
DOI: 10.1016/j.proenv.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Classification for Mangrove Land Cover Mapping Using Landsat 5 TM and Alos Palsar Imageries

Abstract: The objective of this research was to evaluate the accuracy of random forest classification rule using object based image analysis (OBIA) application (eCognition Developer) and the results were compared with common pixel-based classification algorithm (maximum likelihood/ML) for mangrove land cover mapping in Kembung River, Bengkalis Island, Indonesia. Seven data input model derived from Landsat 5TM bands, ALOS PALSAR FBD, and spectral transformations (NDVI, NDWI, NDBI) were examined by both classifiers. Featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 15 publications
1
67
1
4
Order By: Relevance
“…They are based on expert knowledge of the known characteristics of land cover classes, such as urban, vegetation, and water. Thus, we adopt three popular spectral indices: the normalized difference built-up index (NDBI) [29], the normalized difference vegetation index (NDVI) [30], and the modified normalized difference water index (MNDWI) [31], which are a recommended feature combination for land cover classification in [32]. These three spectral indices are closely related to the land cover classes defined in our research; and their formulas are summarized in Table 2.…”
Section: Preprocessingmentioning
confidence: 99%
“…They are based on expert knowledge of the known characteristics of land cover classes, such as urban, vegetation, and water. Thus, we adopt three popular spectral indices: the normalized difference built-up index (NDBI) [29], the normalized difference vegetation index (NDVI) [30], and the modified normalized difference water index (MNDWI) [31], which are a recommended feature combination for land cover classification in [32]. These three spectral indices are closely related to the land cover classes defined in our research; and their formulas are summarized in Table 2.…”
Section: Preprocessingmentioning
confidence: 99%
“…The ML approach is one of the classical parametric statistical classifiers and is widely used for LULC classification [53]. Several studies have also evaluated alternative, recently-developed machine-learning algorithms for land-cover classification, such as support vector machine (SVM) methods [54], decision trees (DT) [55], and random-forest models (RF) [56,57]. Schneider [55] observed that the DT and SVM classifiers outperformed the ML classifier in the context of highly dynamic land-cover change and 'fuzzy' multi-signal classes around the Chinese cities of Chengdu, Xi'An, and Kunming.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Light detection and ranging (LiDAR) and optical remote sensing combined with the support vector machine (SVM) algorithm has been used to map and create a mangrove inventory (David, 2015;Pada, 2016). Other remotely sensed data like Landsat and ALOS-PALSAR have also been used to map mangroves with the random forest (RF) classification (Jhonnerie, 2015).…”
Section: Introductionmentioning
confidence: 99%